Transmisi dan Transformasi Dakwah (Sebuah Kajian Living Hadis dalam Channel Youtube Nussa Official) - hayati Ridha Hayati (Direktorat Jenderal Bimbingan Masyarakat Islam, 2020)
This paper highlights the Islamic animated series that lately is much loved by children and adults, namely Nussa Rara (an acronym from NusAntara). Nussa Official is a youtube channel that contains animated cartoon edutainment (educational entertainment), carrying themes about Islam which is originated from the Qur'an and Hadith. The revelations and messages of the Prophet are displayed so well that they attract attention and are easily understood by children in contrast to other animated shows in general. The focus of this research is on the theme